2021
DOI: 10.1093/plcell/koab267
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of conserved and variable heat and cold stress response in maize using cis-regulatory information

Abstract: Changes in gene expression are important for responses to abiotic stress. Transcriptome profiling of heat- or cold-stressed maize genotypes identifies many changes in transcript abundance. We used comparisons of expression responses in multiple genotypes to identify alleles with variable response to heat or cold stress and to distinguish examples of cis- or trans-regulatory variation for stress-responsive expression changes. We used motifs enriched near the transcription start sites for thermal stress-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 81 publications
4
52
0
Order By: Relevance
“…B144 depicted up-accumulation of several metabolites, viz., flavonoids, lipids, amino acids, alkaloids, and phenolic acids under induced cold stress. Several studies have suggested genotype-dependent regulatory responses under abiotic stresses [61][62][63][64]. Survival strategies under a stress environment highly depend on vegetative growth regulation and hormonal distribution [65].…”
Section: Discussionmentioning
confidence: 99%
“…B144 depicted up-accumulation of several metabolites, viz., flavonoids, lipids, amino acids, alkaloids, and phenolic acids under induced cold stress. Several studies have suggested genotype-dependent regulatory responses under abiotic stresses [61][62][63][64]. Survival strategies under a stress environment highly depend on vegetative growth regulation and hormonal distribution [65].…”
Section: Discussionmentioning
confidence: 99%
“…With a clearer picture of the composition of the SvHSF gene family, we proceeded to assess whether orthologous HSF TFs would respond similarly to heat stress. To address this, we conducted RNA-seq experiments on control and heat stressed Setaria seedlings, matching growth, stress, and sampling conditions with a previously published maize dataset (Zhou et al ., 2021). We identified 1,941 upregulated and 986 downregulated genes in response to a one-hour, 10°C increase over ambient heat stress (Figure 2A-B, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Several of these examples show evidence for a heat response in maize but it was not statistically significant (Figure S6). A prior study monitoring heat responses in maize (Zhou et al ., 2021) generated unreplicated time-course data for responses to heat stress and included a 30-minute time point. Three of the maize genes ( HSFA2b, HSFA2d , and HSFB2a ) from sub-families classified as having Setaria -specific responses exhibit striking up-regulation in response to heat stress at 30 minutes, but the response has largely subsided by 1 hour and the genes are not detected as significant at 1 hour.…”
Section: Resultsmentioning
confidence: 99%
“…This study highlighted the importance of miRNAs in the maize response to cold stress. Combined with large-scale bioinformatic analysis, Zhou et al ( 2022 ) examined the transcriptome changes in seedlings of the inbred lines B73, Mo17, and W22 and the F 1 hybrids with all three combinations (B73xMo17, W22xB73, and W22xMo17) in response to cold or heat stress. They identified many stress-related DEGs among the different maize genotypes and assigned these expression changes to cis-or trans-regulatory mechanisms using the F 1 hybrid data.…”
Section: Genetic and Genomic Approaches To Dissect Cold Tolerance In ...mentioning
confidence: 99%